THE ROLE OF MODERN PEDAGOGICAL TECHNOLOGIES IN TEACHING DIDACTIC LITERARY WORKS AT PRIMARY SCHOOL (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2023)
This paper presents the advantages of using didactic literary works in primary classes and some examples of methods that can be used in this process.